Pelatihan Dasar Software SketchUp Kepada Remaja RT.04 RW.01 Desa Pepe Kecamatan Tegowanu Kabupaten Grobogan - Taufiq Zuda Nasukha; Ahmad Hakim Bintang Kuncoro; Diah Rahmawati; Talitha Zhafira (Jurnal Pengabdian KOLABORATIF, 2023)
The world of education is one of the sectors that has been affected and has undergone drastic changes in teaching and learning activities from face-to-face to online. The activities that students must participate in, namely the student study service (KKN), must also be carried out independently around their environment. In the current pandemic situation, teenagers in the village have much free time that can be filled with beneficial activities and increase knowledge and abilities, so it is necessary to carry out additional skills training. This KKN is a community service activity carried out by one of the students of the Civil Engineering Department, Faculty of Engineering, Universitas Semarang is conducting basic SketchUp software training for teenagers in RT.04 RW.01 Pepe Village, Tegowanu District, Grobogan Regency. KKN students conduct training by making videos to explain the material and doing hands-on practice from house to house with several teenagers in the village. The teenagers seemed enthusiastic and interested in the software used and in the world of civil engineering and architecture. The activity went smoothly and provided benefits in increasing knowledge and abilities after training.